Modeling maize and soybean responses to climatic change and soil degradation in a region of South America. (21st March 2021) - Casali, Lucía; Herrera, Juan M.; Rubio, Gerardo
Abstract: Climatic change effects on crop yields are expected to be crop‐ and site specific. Here, Decision Support System for Agrotechnology Transfer models were used to evaluate climatic change effects and mitigation strategies on maize ( Zea mays L.) and soybean [ Glycine max  (L.) Merr.] yields in soils of the subtropical and semi‐arid region of Chaco. Simulations were performed for the DK747 and A8000 genotypes, calibrated for the CERES‐Maize model in a previous report and for the CROPGRO‐Soybean model in the present study, respectively. Both crops markedly differ in their response to climatic change and putative levels of atmospheric CO2 concentration. The observed significant reductions in maize yields in future climate scenarios (5–42% compared with the baseline, 1986–2010) were more associated with increased temperatures that shortened the crop cycle than with water stress. Delaying the sowing date is a feasible strategy to mitigate this effect. Projected temperature increases are expected to play a secondary role in determining soybean yields. Instead, water stress will continue to be an important constraint to soybean yield in the context of global warming, but this effect is strongly affected by rainfall regimes. Responses to raising CO2 levels were more pronounced in soybean (+10–40%) than in maize (+2–4%). Soil degradation exacerbated the negative effects of global warming on crop yields, especially on maize, which highlights the importance of soil conservation practices. The observed high interannual climatic variability and the different sensitivities of maize and soybean to climatic variables indicate that crop diversification would be the key to improve the resilience of the agrosystems under the future scenarios. Core Ideas: We studied climate change by soil degradation interactions on maize and soybean. Soil degradation exacerbated negative effects on crop yields, especially on maize. Soil conservation practices help mitigate the impacts of climate change. Crop diversification is essential to improve the resilience to climate change.